The Role of Indonesian Constitutional Court in Strengthening Welfare State and the Rule of Law - Usman, Anwar (Lex Publica, 2020)
The conception of the rule of law adopted by the 1945 Constitution is obtained from both the rechtsstaat and the rule of law. It is even obtained from other integrative legal systems, and their implementation is adjusted to the demands of needs and developments. The Amendment of the 1945 Constitution that occurred in Indonesia in 1999–2002, which gave birth to the Constitutional Court, was the right momentum to build Indonesian civilization and state administration towards a constitutional state of law. As the state’s supreme law, the Constitution must be the basis and guideline for all state elements in running the wheels of state organization. The role of the Constitutional Court is important to keep the values ​​contained in the Constitution implemented in accordance with its rules. The dynamics of the development of the Indonesian nation have created challenges and demands for handling various unresolved problems. One of them is the implementation of social security for all Indonesian people as mandated by the 1945 Constitution and the state foundation, Pancasila. The development of a legal culture or culture is unavoidable if the law is expected to be the commander in chief in a country based on the principle of the rule of law (rechtsstaat/the rule of law). As the basic law (groundwet) for the Indonesian state, the 1945 Constitution must be guided and implemented by all elements, both state administrators and citizens, in carrying out their respective duties. Because the establishment of a constitution in a country basically it really depends on the commitment of every citizen. Abstrak Konsepsi negara hukum yang dianut oleh UUD 1945 diperoleh baik dari rechtsstaats maupun rule of law. Bahkan diperoleh dari sistem hukum lain yang bersifat integratif dan pelaksanaannya disesuaikan dengan tuntutan kebutuhan dan perkembangan. Perubahan UUD 1945 yang terjadi di Indonesia pada tahun 1999–2002 yang melahirkan Mahkamah Konstitusi merupakan momentum yang tepat untuk membangun peradaban dan ketatanegaraan Indonesia menuju negara hukum yang konstitusional. Konstitusi sebagai hukum dasar negara (the Supreme law of the land) harus menjadi dasar dan pedoman bagi seluruh elemen negara, dalam menjalankan roda penyelenggaraan negara. Peran MK penting untuk menjaga agar nilai-nilai yang terkandung dalam konstitusi dilaksanakan sesuai dengan aturannya. Dinamika pembangunan bangsa Indonesia telah menimbulkan tantangan dan tuntutan untuk penanganan berbagai permasalahan yang belum terselesaikan. Salah satunya adalah penyelenggaraan jaminan sosial bagi seluruh rakyat Indonesia sebagaimana diamanatkan oleh UUD 1945 dan dasar negara Pancasila. Perkembangan budaya atau budaya hukum tidak dapat dihindarkan jika hukum diharapkan menjadi panglima tertinggi dalam suatu negara berdasarkan prinsip negara hukum (rechstaat/rule of law). Sebagai hukum dasar (groundwet) bagi negara Indonesia, UUD 1945 harus dipedomani dan dilaksanakan oleh semua elemen, baik penyelenggara negara maupun warga negara dalam menjalankan tugasnya masing-masing. Karena pembentukan konstitusi di suatu negara, pada dasarnya sangat tergantung pada komitmen setiap warga negara. Kata kunci: Mahkamah Konstitusi, Konstitusi, Ketatanegaraan, Negara Kesejahteraan, Negara Hukum, Indonesia